Addressing global environmental challenges to mental health using population neuroscience: a review - Schumann, Gunter; Andreassen, Ole A.; Banaschewski, Tobias; Calhoun, Vince D.; Clinton, Nicholas; Desrivieres, Sylvane; Brandlistuen, Ragnhild Eek; Feng, Jianfeng; Hese, Soeren; Hitchen, Esther; Hoffmann, Per; Jia, Tianye; et al. (JAMA psychiatry, 2023)
Climate change, pollution, urbanization, socioeconomic inequality, and psychosocial effects of the COVID-19 pandemic have caused massive changes in environmental conditions that affect brain health during the life span, both on a population level as well as on the level of the individual. How these environmental factors influence the brain, behavior, and mental illness is not well known.A research strategy enabling population neuroscience to contribute to identify brain mechanisms underlying environment-related mental illness by leveraging innovative enrichment tools for data federation, geospatial observation, climate and pollution measures, digital health, and novel data integration techniques is described. This strategy can inform innovative treatments that target causal cognitive and molecular mechanisms of mental illness related to the environment. An example is presented of the environMENTAL Project that is leveraging federated cohort data of over 1.5 million European citizens and patients enriched with deep phenotyping data from large-scale behavioral neuroimaging cohorts to identify brain mechanisms related to environmental adversity underlying symptoms of depression, anxiety, stress, and substance misuse.This research will lead to the development of objective biomarkers and evidence-based interventions that will significantly improve outcomes of environment-related mental illness.
Veröffentlicht: 23. August 2023
Gesehen am 15.11.2023